Non-pharmacological Management of Non-productive Chronic Cough in Adults: A Systematic Review - Ilicic, Ana Maria; Oliveira, Ana; Habash, Razanne; Kang, Yejin; Kho, Michelle; Goldstein, Roger; Brooks, Dina (Frontiers in Rehabilitation Sciences, 2022)
Background. Chronic cough is a common reason for medical referral and its prevalence is on the rise. With only one pharmaceutical therapy currently under review for the treatment of refractory chronic cough, exploring non-pharmacological chronic cough management therapies is important. This systematic review summarizes the effectiveness of non-pharmacological chronic cough therapies in adults with non-productive refractory chronic cough or cough due to chronic respiratory diseases. Methods. We searched Medline, Embase, Cochrane, CINAHL, and Scopus from inception to September 2021. Randomized controlled trials published in English, Portuguese, or French, and examining the effects of non-pharmacological therapies in adults with chronic non-productive cough (>8 weeks; <2 teaspoons sputum) were included. Mean differences, medians, and odds ratios were calculated as appropriate. Results. 16,546 articles were identified and six articles representing five unique studies were included. Studies evaluated 228 individuals with refractory chronic cough or chronic cough due to a chronic respiratory disease (162 women (71%); 52±11 to 61±8 years old). Obstructive sleep apnea was the only chronic respiratory disease studied. Non-pharmacological therapies included education, cough suppression, breathing techniques, mindfulness, and continuous positive airway pressure. When standing alone, non-pharmacological cough therapies improved cough-specific health related quality of life when not associated with interventions (mean diff MD 1.53 to 4.54), cough frequency (MD 0.59 95%CI 0.36 to 0.95), and voice outcomes (MD 0.3 to 1) when compared to control interventions. Conclusion. The evidence of non-pharmacological therapies for non-productive chronic cough is limited. Existing studies reflect the heterogeneity in study design, sample size, and outcome measures. Thus, clinical recommendations for using the most effective interventions remain to be confirmed.